How Macroeconomic and Fundamental Factors Influence Stock Prices of Major Banks in Indonesia ? - Vinda Cendrawati; Arief Bachtiar (Yayasan Riset dan Pengembangan Intelektual, 2024)
This study investigates the relationship between global macroeconomic variables and fundamental factors with the stock price performance of the banking sector in Indonesia. It is motivated by the significant impact of recent economic changes, particularly in the aftermath of the COVID-19 pandemic. Utilizing quantitative research methods, panel data regression analysis is employed to analyze the influence of various independent variables, including US inflation, Federal Reserve Rate, Indonesian inflation, BI Rate, Net Interest Margin, and Return on Equity, on the stock prices of the KBMI 4 banking sector. The research data, collected from secondary sources such as BPS, Otoritas Jasa Keuangan, Bank Indonesia, Bloomberg, and Investing.com, spans from 2013 to 2023. The findings aim to provide valuable insights for investors, analysts, and policymakers in understanding and responding to global economic challenges and making informed investment decisions.